2017
DOI: 10.1128/aac.00020-17
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminopyrazole-4-Carboxamide-Based Compounds Prevent the Growth of Cryptosporidium parvum

Abstract: Cryptosporidium parvum calcium-dependent protein kinase 1 (CpCDPK1) is a promising target for drug development against cryptosporidiosis. We report a series of low-nanomolar CpCDPK1 5-aminopyrazole-4-carboxamide (AC) scaffold inhibitors that also potently inhibit C. parvum growth in vitro. Correlation between anti-CpCDPK1 and C. parvum growth inhibition, as previously reported for pyrazolopyrimidines, was not apparent. Nonetheless, lead AC compounds exhibited a substantial reduction of parasite burden in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
1
23
2
Order By: Relevance
“…However, CpCDPK1 has been shown to be involved in C. parvum invasion rather than growth (Castellanos-Gonzalez et al, 2016;Kuhlenschmidt et al, 2016). Although a recent study has shown that some candidate CpCDPK1 inhibitors could potently inhibit C. parvum growth in vitro, there was no apparent correlation between anti-CpCDPK1 activities and C. parvum growth inhibition (Huang et al, 2017). In contrast, data generated with candidate inhibitors in the present study suggest that CpCDPK3 is involved in C. parvum growth but not invasion.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, CpCDPK1 has been shown to be involved in C. parvum invasion rather than growth (Castellanos-Gonzalez et al, 2016;Kuhlenschmidt et al, 2016). Although a recent study has shown that some candidate CpCDPK1 inhibitors could potently inhibit C. parvum growth in vitro, there was no apparent correlation between anti-CpCDPK1 activities and C. parvum growth inhibition (Huang et al, 2017). In contrast, data generated with candidate inhibitors in the present study suggest that CpCDPK3 is involved in C. parvum growth but not invasion.…”
Section: Discussioncontrasting
confidence: 89%
“…Most previous studies of CDPKs of C. parvum (CpCDPKs) are on CpCDPK1, which is expressed in all life cycle stages, and believed to play an important role in the invasion (Castellanos-Gonzalez et al, 2016;Kuhlenschmidt et al, 2016) and possibly growth of C. parvum (Huang et al, 2017). In comparison, the function of CpCDPK3, which shares high structural homology with CpCDPK1, is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…1112 Solubility tests for all inhibitors were determined at pH 2 and pH 6.5 as previously described. 10…”
Section: Methodsmentioning
confidence: 99%
“…68 Selective targeting of Cryptosporidium parvum CDPK1 ( Cp CDPK1) with “bumped kinase inhibitors” (BKIs) based on 1 H -pyrazolo[3,4- d ]pyrimidin-4-amine (pyrazolopyrimidine, PP) and 5-aminopyrazole-4-carboxamide (AC) chemical scaffolds blocks parasite cell proliferation in both in vitro and in vivo models of cryptosporidiosis. 610 Partial knockdown of Cp CDPK1 with small interfering RNAs (siRNAs) led to significantly decreased C. parvum parasite invasion and growth. Moreover, partial Cp CDPK1 siRNA knockdown in combination with treatment of either BKIs 1294 (PP) or 1517 (AC) produced further inhibitory effects on the proliferation of C. parvum parasites.…”
mentioning
confidence: 99%
“…These efforts have led to the identification of numerous promising lead compounds and two pre-clinical candidates that are poised for human studies (i.e. a Novartis phosphatidyl-inositol-4-kinase inhibitor and the 6-carboxamide benzoxaborole AN7973) (12)(13)(14)(15)(16)(17)(18)(19)(20). There is the potential to realize an enormous public health benefit with intelligent deployment of improved anticryptosporidial drugs.…”
Section: Introductionmentioning
confidence: 99%